Developing Best Practices for Evaluating Fluid Saturations with Pulsed Neutron Capture Logging Across Multiple Active CO2-EOR Fields. (July 2017) - Conner, Amber; Chace, David; Abou-Saleh, Jehad; Kim, Yonghwee; McNeil, Caitlin; Gerst, Jacqueline; Kelley, Mark; Place, Matt; Pardini, Rick; Gupta, Neeraj
Abstract: The Midwest Regional Carbon Sequestration Partnership (MRCSP) is leading an extensive study and monitoring effort of large-scale carbon dioxide (CO2 ) injection and storage during enhanced oil recovery (EOR) in depleted oil fields in the Michigan Niagara Reef Trend. Detailed monitoring of caprock and reservoir zones is vital for understanding oil, gas, and water saturations and potential migration of CO2 . Baseline and repeat pulsed neutron capture (PNC) logs were collected as part of the monitoring effort and study for these storage sites. An overview of the development and enhancement of best practices for PNC logging in complex EOR fields is presented.